2014
DOI: 10.1177/0363546514544684
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analyses in Orthopaedic Sports Medicine

Abstract: The CEA literature in sports medicine is good; however, there is a paucity of studies, and the available evidence is focused on a few procedures. More work needs to be conducted to quantify the cost-effectiveness of different techniques and procedures within sports medicine. The QHES tool may be useful for the evaluation of future CEAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 47 publications
3
98
0
Order By: Relevance
“…When examining the studies with the validated QHES instrument, we found similarly mixed reporting, with a mean score of 79.7, and mean adherence rates for specific parameters ranging from 41% (explicit discussion of biases) to 100% (conclusions based on study results). These results are similar to those reported in a review of orthopaedic sports literature (mean of 81.8) [14]. When analyzed by strength of recommendations, there appear to be few differences in reporting practices.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…When examining the studies with the validated QHES instrument, we found similarly mixed reporting, with a mean score of 79.7, and mean adherence rates for specific parameters ranging from 41% (explicit discussion of biases) to 100% (conclusions based on study results). These results are similar to those reported in a review of orthopaedic sports literature (mean of 81.8) [14]. When analyzed by strength of recommendations, there appear to be few differences in reporting practices.…”
Section: Discussionsupporting
confidence: 87%
“…Given the importance of cost-effectiveness research in clinical decision and policy-making, understanding the proportions of strong and weak recommendations offered by these studies is imperative. This is especially true given the steadily increasing volume of such studies in the orthopaedic literature [3][4][5]14] and seen again in our study. This approach enables an understanding of the proportion of cost-effectiveness analysis studies that are either lacking in or have uncertainty around key data parameters, which limits the strength of the authors' recommendations.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…1,2 Currently, assessment tools such as the Landing Error Scoring System (LESS) have been described in the literature and adopted by clinicians as valuable tools used to assess knee injury risk. 3 Unfortunately, while these tools have been shown to be valid, they rely on subjective criteria to assess patient performance, which may be affected by clinician experience.…”
Section: Introductionmentioning
confidence: 99%